2010
DOI: 10.1111/j.1469-8137.2010.03357.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of endoreduplication and apomeiosis during parthenogenetic reproduction in the model brown alga Ectocarpus

Abstract: Summary• The filamentous brown alga Ectocarpus has a complex life cycle, involving alternation between independent and morphologically distinct sporophyte and gametophyte generations. In addition to this basic haploid-diploid life cycle, gametes can germinate parthenogenetically to produce parthenosporophytes. This article addresses the question of how parthenosporophytes, which are derived from a haploid progenitor cell, are able to produce meiospores in unilocular sporangia, a process that normally involves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 40 publications
0
81
0
Order By: Relevance
“…For example, several lines of evidence indicated that life cycle generation can be uncoupled from ploidy. Haploid, diploid, or tetraploid partheno-sporophytes (25,26) and haploid, diploid, and aneuploid gametophytes (26)(27)(28) have been observed in culture. Here we have shown that zygotes derived from a cross between male and female oro mutants give rise to functional, diploid gametophytes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several lines of evidence indicated that life cycle generation can be uncoupled from ploidy. Haploid, diploid, or tetraploid partheno-sporophytes (25,26) and haploid, diploid, and aneuploid gametophytes (26)(27)(28) have been observed in culture. Here we have shown that zygotes derived from a cross between male and female oro mutants give rise to functional, diploid gametophytes.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of life cycle progression at the molecular level is accumulating rapidly for Ectocarpus, a brown algal model species with a haploiddiploid life cycle with subtle but distinct morphological differentiation between the sporophyte and gametophyte phases ( Figure 1B). The complex life cycle of Ectocarpus has shown that life cycle transitions are controlled by genetic mechanisms instead of ploidy level, and can show a large degree of developmental plasticity (Müller 1967, Bothwell et al 2010. However the identity of the molecular players is only just being revealed thanks to the combination of a whole genome sequence for Ectocarpus and life cycle mutants .…”
Section: A Molecular Perspective On Fertility Genetic Controlmentioning
confidence: 99%
“…These diploid individuals can then initiate meiotic cell division in the same manner as diploid sporophytes derived from the fusion of two gametes. A complementary bioinformatic analysis of the genome sequence identified a number of genes that potentially play a role in mediating the endoreduplicative cell division (Bothwell et al, 2010b). These results therefore explained how one third of the partheno-sporophytes produce meio-spores, but what about the remaining two thirds?…”
Section: Exploiting the Ectocarpus Genome Sequence To Investigate Bromentioning
confidence: 93%
“…How they are able to do this has been a mystery because meio-spores are normally derived from a meiotic cell division that is followed by several mitotic divisions, and it has been difficult to see how this could occur when the initial cells of the partheno-sporophytes are haploid gametes. However, careful analysis of ploidy levels in the cells of developing partheno-sporophytes indicated that about one third of these individuals underwent an endoreduplication event very early in development (Bothwell et al, 2010a;Bothwell et al, 2010b). These diploid individuals can then initiate meiotic cell division in the same manner as diploid sporophytes derived from the fusion of two gametes.…”
Section: Exploiting the Ectocarpus Genome Sequence To Investigate Bromentioning
confidence: 97%